Types of repetition in Semitic languages ​​: A comparative linguistic study - Razzaq , Lina; Obaid , Haider (Al-Adab Journal, 2025)
Repetition is a linguistic phenomenon known to Arabic in most of its texts that have reached us, starting from the pre-Islamic era until the modern era. It has also been used in the Holy Qur’an, the Noble Hadith, and the speech of the Arabs in poetry and prose, and in the Semitic languages ​​we find repetition of nouns, verbs, letters, and sentences. It is an Arabic term that had its presence among ancient Arab rhetoricians, and it is not based only on the mere repetition of the word in the context, but rather on the emotional impact that the word leaves on the soul of the recipient, and thus reflects an aspect of the psychological and emotional situation, and such an aspect cannot be understood except through studying repetition, which represents one of the  Aesthetic tools that help understand an image scene Or a situation, and also the art of my speech, is one of the methods known to the Arabs. Rather, it is one of the virtues of eloquence and a method of emphasis in the Arabic language that comes to document the meaning as well as prove it, and also one of the most important means of persuasion, and as mentioned above, the Arabs knew it in their speech, and it came in the Holy Qur’an adopting that method such that  The soul does not tire of it, nor does the call to prayer turn away from it. It is intended to be brief and short. Therefore, it is considered consolidation and confirmation, and it is also considered one of the means of consolidation and persuasion, as well as acknowledgment. This is why it is considered the closest to doubt or certainty and the most powerful. .  It appears in the Holy Qur’an in different styles depending on the context.  On this basis, Arabic rhetoric viewed repetition in terms of emphasis and used it to emphasize and consolidate meanings, which have a role in achieving formal and semantic coherence in a specific communicative context between recurring elements within the text. So, through this, its repetition is achieved with the purposes and meanings it carries, as it is a form of lexical cohesion, and it is one of the phenomena that characterizes languages ​​in general and the Arabic language in particular, “which we find in words, structures, and meanings to achieve eloquence in expression and to emphasize speech and beauty in linguistic performance.